Ultraviolet-curable resin composition, optical component, method for manufacturing optical component, light-emitting device, and method for manufacturing light-emitting device
A UV curable resin composition with a high water-soluble compound ratio and low viscosity is used to form a flat and smooth film on inorganic materials, addressing the issue of surface deterioration in thin light emitting devices and improving performance.
Patent Information
- Application Number
- JP2020159020
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-23
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-09-23
AI Technical Summary
As light emitting devices become thinner, the encapsulant thickness is reduced, leading to deteriorated flatness and smoothness of the surface, which affects the light emitting performance.
A UV curable resin composition containing a photopolymerizable compound with a water-soluble compound at a ratio of 10% by mass or more and a viscosity of 30 mPa·s or less, applied using an inkjet method and cured with UV rays, to form a flat and smooth film on inorganic materials.
The composition ensures a flat and smooth surface even on uneven inorganic materials, reducing defects and enhancing light emitting performance while maintaining low viscosity for precise application.
Smart Images

Figure 0007599145000026 
Figure 0007599145000001 
Figure 0007599145000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an ultraviolet-curable resin composition, an optical component, a method for manufacturing an optical component, a light-emitting device, and a method for manufacturing a light-emitting device, and more particularly to an ultraviolet-curable resin composition that can be molded by an inkjet method, an optical component made from the ultraviolet-curable resin composition, a method for manufacturing an optical component using the ultraviolet-curable resin composition, a light-emitting device including the optical component, and a method for manufacturing a light-emitting device using the ultraviolet-curable resin composition. [Background technology]
[0002] Light-emitting devices such as organic electroluminescence (EL) devices are used in lighting, displays, and other applications, and are expected to become more widespread in the future.
[0003] A light emitting device is configured, for example, by disposing a light emitting element on a supporting substrate and disposing a transparent substrate opposite the supporting substrate, in which case light emitted by the light emitting element passes through the transparent substrate and is emitted to the outside.
[0004] When light-emitting elements such as organic EL elements deteriorate due to moisture, non-emitting areas called dark spots may occur. For this reason, the light-emitting elements are covered with a transparent sealing material and a passivation layer made of a nitrogen compound to prevent moisture from entering the light-emitting elements from the outside (see Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-186850 A Summary of the Invention [Problem to be solved by the invention]
[0006] In order to reduce the thickness of light-emitting devices, the inventors tried to make the encapsulant thinner when fabricating the encapsulant on a passivation layer, but found that the thinner the encapsulant, the worse the flatness and smoothness of the encapsulant's surface becomes. If the flatness and smoothness of the encapsulant surface deteriorates, the light-emitting performance of the light-emitting device deteriorates.
[0007] An object of the present invention is to provide an ultraviolet-curable resin composition that tends to produce a flat and smooth cured film when cured on an inorganic material, an optical component produced from the ultraviolet-curable resin composition, a method for producing an optical component using the ultraviolet-curable resin composition, a light-emitting device including an optical component, and a method for producing a light-emitting device using the ultraviolet-curable resin composition. [Means for solving the problem]
[0008] An ultraviolet-curable resin composition according to one embodiment of the present invention contains a photopolymerizable compound (A) and a photopolymerization initiator (B). The photopolymerizable compound (A) contains a water-soluble compound (C), and the percentage of the water-soluble compound (C) relative to the ultraviolet-curable resin composition is 10 mass % or more. The viscosity of the ultraviolet-curable resin composition at 25°C is 30 mPa s or less.
[0009] An optical component according to one aspect of the present invention includes a cured product of the ultraviolet-curable resin composition.
[0010] A method for producing an optical component according to one aspect of the present invention includes molding the ultraviolet-curable resin composition by an inkjet method, and then irradiating the ultraviolet-curable resin composition with ultraviolet light to cure it.
[0011] A light emitting device according to one aspect of the present invention includes a light source and an optical component that transmits light emitted from the light source. The optical component includes a cured product of the ultraviolet curable resin composition.
[0012] A method for manufacturing a light emitting device according to one aspect of the present invention is a method for manufacturing a light emitting device including a light source and an optical component that transmits light emitted by the light source, the method including manufacturing the optical component by the method for manufacturing the optical component. Effect of the Invention
[0013] According to one aspect of the present invention, there are provided an ultraviolet-curable resin composition that tends to become flat and smooth when formed into a film on an inorganic material, an optical component made from the ultraviolet-curable resin composition, a method for manufacturing an optical component using the ultraviolet-curable resin composition, a light-emitting device including an optical component, and a method for manufacturing a light-emitting device using the ultraviolet-curable resin composition. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic cross-sectional view showing an example of a light-emitting device according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, one embodiment of the present invention will be described.
[0016] The ultraviolet-curable resin composition according to this embodiment (hereinafter also referred to as composition (X)) contains a photopolymerizable compound (A) and a photopolymerization initiator (B). The photopolymerizable compound (A) contains a water-soluble compound (C). The percentage of the water-soluble compound (C) relative to the composition (X) is 10 mass % or more. The viscosity of the composition (X) at 25°C is 30 mPa s or less.
[0017] The water-soluble compound (C) is a compound that is photopolymerizable and water-soluble. The water-soluble compound refers to a compound that, when mixed with an equal volume of pure water at 20°C under 1 atmosphere to prepare a mixed liquid, and the mixed liquid is gently stirred and then allowed to stand, the mixed liquid maintains a uniform appearance even after the flow of the mixed liquid has subsided.
[0018] According to this embodiment, the affinity between the composition (X) and inorganic materials such as silicon nitride can be increased by the water-soluble compound (C), and the viscosity of the composition (X) is 30 mPa·s or less, so that the fluidity of the composition (X) can be increased. Therefore, when the composition (X) is applied onto an inorganic material such as silicon nitride to form a coating film, the surfaces of the coating film and the cured film obtained by curing this coating film tend to be flat and smooth. Therefore, when a cured film is produced from the composition (X) on an inorganic material, even if the surface of the inorganic material has irregularities and the thickness of the cured film is small, the cured film tends to be flat and smooth.
[0019] The percentage of the water-soluble compound (C) relative to the composition (X) is more preferably 10% by mass or more, and even more preferably 15% by mass or more. The percentage of the water-soluble compound (C) relative to the composition (X) is preferably 50% by mass or less. In this case, outgassing due to volatilization of the water-soluble compound (C) from the composition (X) and the cured product is suppressed. The percentage of the water-soluble compound (C) is more preferably 40% by mass or less, and even more preferably 30% by mass or less.
[0020] Composition (X) can be used to manufacture optical components, and can also be used to manufacture light-emitting devices equipped with optical components. The use of composition (X) is not limited to the manufacture of optical components, and composition (X) can be used in a variety of applications that utilize the properties of composition (X).
[0021] The composition (X) is preferably molded by an inkjet method. In this case, it is easy to prepare a cured product of the composition (X) with good positional accuracy. In addition, compared with molding by a printing method involving contact such as a screen printing method, when the composition (X) is molded by an inkjet method, foreign matter is less likely to be mixed into the composition (X) and its cured product, and therefore the yield in manufacturing optical parts is less likely to deteriorate. In this embodiment, as described above, the viscosity of the composition (X) at 25°C is 30 mPa·s or less, so that the composition (X) is easily molded by an inkjet method. It is more preferable that this viscosity is 25 mPa·s or less, even more preferable that it is 20 mPa·s or less, and particularly preferable that it is 15 mPa·s or less. It is also preferable that this viscosity is 1 mPa·s or more, and it is also preferable that it is 5 mPa·s or more.
[0022] Such a low viscosity of composition (X) can be achieved by the composition (X) described in detail below. The method and conditions for measuring the viscosity will be described in detail in the Examples section below.
[0023] It is preferable that the outgassing rate generated when the cured product of the composition (X) is heated at 100°C for 30 minutes is 200 ppm or less. In this case, outgassing is unlikely to occur from the cured product. Therefore, for example, it is possible to make it difficult for voids due to outgassing to occur in a light-emitting device equipped with an optical component containing the cured product. Therefore, it is difficult for water and oxygen to reach the light-emitting element through the voids, and the light-emitting element is unlikely to deteriorate due to water and oxygen. It is more preferable that the outgassing rate is 100 ppm or less, and even more preferable that it is 50 ppm or less. The method and conditions for measuring the outgassing rate will be described in detail in the Examples section below.
[0024] It is preferable that the composition (X) does not contain a solvent or the content of the solvent is 1% by mass or less. In this case, outgassing derived from the solvent is unlikely to occur from the composition (X) and the cured product of the composition (X). In addition, a drying process for removing the solvent from the composition (X) and the cured product during the production of the optical component and the light emitting device can be eliminated. A drying process for removing the solvent from at least one of the composition (X) and the cured product may be performed. In this case, at least one of the heating temperature and the heating time in the drying process can be reduced. Therefore, outgassing can be unlikely to occur from the optical component without reducing the production efficiency of the optical component and the light emitting device. Furthermore, when the composition (X) is molded, especially by the inkjet method, the thickness is unlikely to decrease due to the evaporation of the solvent from the composition (X) after molding, and therefore the thickness of the optical component is unlikely to decrease. Therefore, the thickness of the optical component can be secured as large as possible while molding by the inkjet method. The content of the solvent is more preferably 0.5% by mass or less, even more preferably 0.3% by mass or less, and particularly preferably 0.1% by mass or less. It is particularly preferred that the composition (X) does not contain a solvent or contains only an unavoidably mixed solvent.
[0025] The glass transition temperature of the cured product of the composition (X) is preferably 80° C. or higher. That is, the composition (X) preferably has a property of curing to become a cured product having a glass transition temperature of 80° C. or higher. In this case, the cured product can have good heat resistance. Therefore, for example, when the cured product is subjected to a treatment accompanied by a temperature increase, the cured product is not easily deteriorated. Therefore, for example, when an inorganic material layer (e.g., passivation layer 6) that overlaps an optical component is produced by a deposition method such as a plasma CVD method, the optical component is not easily deteriorated even if the optical component is heated. In addition, by increasing the heat resistance, the optical component can be adapted to an in-vehicle application that has strict requirements for heat resistance. The glass transition temperature of the cured product is more preferably 100° C. or higher, and even more preferably 120° C. or higher. This glass transition temperature of the cured product can be achieved by the composition of the composition (X) described in detail below.
[0026] The volatility of 20 mg of composition (X) is preferably 40% or less when heated at 100°C for 30 minutes using a thermogravimetric analyzer. The volatility of composition (X) is defined as the percentage of the weight loss of composition (X) after treatment (the difference between the weight of composition (X) before treatment and the weight of composition (X) after treatment) relative to the weight of composition (X) before treatment. In this case, the low volatility of composition (X) can enhance the storage stability of composition (X). In addition, outgassing is less likely to occur from the cured product of composition (X) and optical components. Therefore, voids due to outgassing are further less likely to occur in the light-emitting device. The volatility of composition (X) can be determined by heating 20 mg of composition (X) at 100°C for 30 minutes using a thermogravimetric analyzer and calculating the weight loss of the weight after treatment relative to the weight before treatment. When 20 mg of composition (X) is heated at 100° C. for 30 minutes using a thermogravimetric analyzer, the volatility is more preferably 30% or less, and even more preferably 20% or less. The lower limit of the volatility of composition (X) is not particularly limited, but may be, for example, 0.1% or more.
[0027] The components contained in the composition (X) will be described in more detail below.
[0028] The photopolymerizable compound (A) is a compound capable of undergoing a polymerization reaction upon irradiation with ultraviolet light. The photopolymerizable compound (A) contains, for example, at least one component selected from the group consisting of monomers, oligomers, and prepolymers.
[0029] The photopolymerizable compound (A) contains, for example, at least one of a radically polymerizable compound (A1) and a cationic polymerizable compound (A2). When the photopolymerizable compound (A) contains a radically polymerizable compound (A1), the photopolymerization initiator (B) preferably contains a photoradical polymerization initiator (B1). When the photopolymerizable compound (A) contains a cationic polymerizable compound (A2), the photopolymerization initiator (B) preferably contains a photocationic polymerization initiator (B2) (cationic curing catalyst).
[0030] When the photopolymerizable compound (A) contains a radically polymerizable compound (A1), the radically polymerizable compound (A1) preferably contains an acrylic compound (Y). The acrylic compound (Y) has one or more (meth)acryloyl groups in one molecule.
[0031] The acrylic compound (Y) preferably contains a polyfunctional acrylic compound (Y1) having two or more radically polymerizable functional groups including a (meth)acryloyl group in one molecule. In this case, the polyfunctional acrylic compound (Y1) can increase the glass transition temperature of the cured product, and therefore can increase the heat resistance of the cured product. The percentage of the polyfunctional acrylic compound (Y1) is preferably 50% by mass or more and 100% by mass or less based on the total amount of the acrylic compound (Y). The acrylic compound (Y) may contain only the polyfunctional acrylic compound (Y1).
[0032] The polyfunctional acrylic compound (Y1) may contain a compound (Y11) having a structure represented by the following formula (200).
[0033] CH 2 =CR 1 -COO-(R 3 -O)n-CO-CR 2 =CH 2 …(200) In formula (200), R 1 and R 2 Each of the groups is a hydrogen atom or a methyl group, n is an integer of 1 or more, R 3 is an alkylene group having 1 or more carbon atoms, and when n is 2 or more, multiple R 3may be the same or different. The percentage of the compound (Y11) relative to the acrylic compound (Y) is preferably 50% by mass or more. In this case, the affinity of the cured product to water is particularly difficult to increase. The percentage of the compound (Y11) relative to the acrylic compound (Y) is, for example, 100% by mass or less, or 95% by mass or less, preferably 80% by mass or less. The compound (Y11) contains at least one compound selected from the group consisting of, for example, alkylene glycol di(meth)acrylate, polyalkylene glycol di(meth)acrylate, and alkylene oxide modified alkylene glycol di(meth)acrylate.
[0034] It is particularly preferred that the polyfunctional acrylic compound (Y1) contains polyalkylene glycol di(meth)acrylate. Since polyalkylene glycol di(meth)acrylate has low viscosity and is not easily volatile, it can contribute to lowering the viscosity of the composition (X), improving the storage stability of the composition (X), and reducing outgassing from the cured product. The percentage of polyalkylene glycol di(meth)acrylate to the acrylic compound (Y) is preferably 40% by mass or more and 80% by mass or less.
[0035] The polyfunctional acrylic compound (Y1) may contain a compound having three or more radically polymerizable functional groups including a (meth)acryloyl group in one molecule. In this case, the polyfunctional acrylic compound (Y1) may contain at least one selected from the group consisting of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, and pentaerythritol tetra(meth)acrylate. In this case, the glass transition temperature of the cured product can be particularly increased, and therefore the heat resistance of the cured product can be particularly increased. The polyfunctional acrylic compound (Y1) preferably contains pentaerythritol tetra(meth)acrylate. The percentage of pentaerythritol tetra(meth)acrylate relative to the acrylic compound (Y) is preferably 0.5% by mass or more and 10% by mass or less.
[0036] The acrylic compound (Y) preferably contains a monofunctional acrylic compound (Y2) in which the radical polymerizable functional group in one molecule is only one (meth)acryloyl group. The monofunctional acrylic compound (Y2) can suppress the shrinkage during curing of the composition (X). The amount of the monofunctional acrylic compound (Y2) relative to the total amount of the acrylic compound (Y) is preferably more than 0 mass% and 50 mass% or less.
[0037] Examples of the monofunctional acrylic compound (Y2) include tetrahydrofurfuryl acrylate, isobornyl acrylate, 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, isobutyl acrylate, t-butyl acrylate, isooctyl acrylate, 2-methoxyethyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, 3-methoxybutyl acrylate, ethoxyethyl acrylate, butoxyethyl acrylate, ethoxydiethylene glycol acrylate, and methacrylate. Toxidixylethyl acrylate, ethyl diglycol acrylate, cyclic trimethylolpropane formal monoacrylate, imide acrylate, isoamyl acrylate, ethoxylated succinic acid acrylate, trifluoroethyl acrylate, ω-carboxypolycaprolactone monoacrylate, cyclohexyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, stearyl acrylate, diethylene glycol monobutyl ether acrylate, lauryl acrylate, isodecyl acrylate, 3,3,5-trimethylcyclohexanol acrylate, isooctyl acrylate, octyl / decyl acrylate, tridecyl acrylate, caprolactone acrylate, ethoxylated (4) nonylphenol acrylate, methoxypolyethylene glycol (350) monoacrylate, methoxypolyethylene glycol (550) monoacrylate, phenoxyethyl acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl acrylate, methylphenoxyethyl acrylate, 4-t-butylcyclohexyl acrylate, caprolactone modified tetrahydrofurfuryl acrylate, tributary The composition contains at least one compound selected from the group consisting of bromophenyl acrylate, ethoxylated tribromophenyl acrylate, 2-phenoxyethyl acrylate, an ethylene oxide adduct of 2-phenoxyethyl acrylate, a propylene oxide adduct of 2-phenoxyethyl acrylate, acryloylmorpholine, morpholin-4-yl acrylate, dicyclopentanyl acrylate, phenoxydiethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 1,4-cyclohexanedimethanol monoacrylate, 3-methacryloyloxymethylcyclohexene oxide, and 3-acryloyloxymethylcyclohexene oxide.
[0038] The acrylic compound (Y) may contain a compound represented by the following formula (100). In this case, the reactivity of the composition (X) can be increased, and the adhesion between the cured product and the inorganic material can be improved.
[0039] [ka]
[0040] In formula (100), R 0 is H or a methyl group. X is a single bond or a divalent hydrocarbon group. R 1 From R 11 Each of is H, an alkyl group or -R 12 -OH, R12 is an alkylene group and R 1 From R 11 At least one of the groups is an alkyl group or -R 12 -OH. 1 From R 11 are not chemically bonded to each other.
[0041] The radical polymerizable compound (A1) may contain a radical polymerizable compound (Z) other than the acrylic compound (Y). The amount of the radical polymerizable compound (Z) relative to the total amount of the acrylic compound (Y) and the polymerizable compound (Z) is, for example, 10 mass% or less.
[0042] When the photopolymerizable compound (A) contains a radically polymerizable compound (A1), the radically polymerizable compound (A1) may contain a radically polymerizable water-soluble compound (C1) which is at least a part of the water-soluble compound (C). The water-soluble compound (C1) includes at least one selected from the group consisting of, for example, HO-250(N), 130MA, EG, and HOA(N) of the Light Ester Series manufactured by Kyoeisha Chemical Co., Ltd., 130A and 3EG-A of the Light Acrylate Series, and methacrylic acid manufactured by Mitsubishi Chemical Corporation.
[0043] The photoradical polymerization initiator (B1) is not particularly limited as long as it is a compound that generates radical species when irradiated with ultraviolet light. The photoradical polymerization initiator (B1) contains at least one compound selected from the group consisting of, for example, aromatic ketones, acylphosphine oxide compounds, aromatic onium salt compounds, organic peroxides, thio compounds (thioxanthone compounds, thiophenyl group-containing compounds, etc.), hexaarylbiimidazole compounds, oxime ester compounds, borate compounds, azinium compounds, metallocene compounds, active ester compounds, compounds having carbon-halogen bonds, and alkylamine compounds.
[0044] The percentage of the photoradical polymerization initiator (B1) relative to the radical polymerizable compound (A1) is preferably 6% by mass or more. This percentage is more preferably 7% by mass or more, and even more preferably 8% by mass or more. This percentage is, for example, 30% by mass or less, preferably 20% by mass or less, and even more preferably 18% by mass or less.
[0045] The photoradical polymerization initiator (B1) may contain a sensitizer as a part of the photoradical polymerization initiator (B1). The sensitizer may contain at least one compound selected from the group consisting of 9,10-dibutoxyanthracene, 9-hydroxymethylanthracene, thioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, anthraquinone, 1,2-dihydroxyanthraquinone, 2-ethylanthraquinone, 1,4-diethoxynaphthalene, p-dimethylaminoacetophenone, p-diethylaminoacetophenone, p-dimethylaminobenzophenone, p-diethylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, p-dimethylaminobenzaldehyde, and p-diethylaminobenzaldehyde. However, the components that the sensitizer can contain are not limited to those mentioned above. The content of the sensitizer in the composition (X) is, for example, 0.1 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the solid content of the composition (X).
[0046] The composition (X) may contain a polymerization accelerator in addition to the photoradical polymerization initiator (B1). The polymerization accelerator contains, for example, an amine compound such as ethyl p-dimethylaminobenzoate, 2-ethylhexyl p-dimethylaminobenzoate, methyl p-dimethylaminobenzoate, 2-dimethylaminoethyl benzoate, or butoxyethyl p-dimethylaminobenzoate. Note that the components that the polymerization accelerator can contain are not limited to those mentioned above.
[0047] When the photopolymerizable compound (A) contains a cationic polymerizable compound (A2), the cationic polymerizable compound (A2) contains, for example, at least one of a polyfunctional cationic polymerizable compound (W1) and a monofunctional cationic polymerizable compound (W2).
[0048] The polyfunctional cationically polymerizable compound (W1) can contain either one or both of a polyfunctional cationically polymerizable compound (W11) having no siloxane skeleton and a polyfunctional cationically polymerizable compound (W12) having a siloxane skeleton.
[0049] The polyfunctional cationically polymerizable compound (W11) does not have a siloxane skeleton and has two or more cationically polymerizable functional groups per molecule. The number of cationically polymerizable functional groups per molecule of the polyfunctional cationically polymerizable compound (W11) is preferably 2 to 4, and more preferably 2 to 3.
[0050] The cationically polymerizable functional group is, for example, at least one group selected from the group consisting of a cyclic ether group and a vinyl ether group. The cyclic ether group is, for example, at least one of an epoxy group and an oxetane group.
[0051] The polyfunctional cationically polymerizable compound (W11) contains at least one compound selected from the group consisting of, for example, polyfunctional alicyclic epoxy compounds, polyfunctional heterocyclic epoxy compounds, polyfunctional oxetane compounds, alkylene glycol diglycidyl ethers, and alkylene glycol monovinyl monoglycidyl ethers.
[0052] The polyfunctional alicyclic epoxy compound contains, for example, either one or both of a compound represented by the following formula (1) and a compound represented by the following formula (20).
[0053] [ka]
[0054] In formula (1), R 1 ~R18 are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably within the range of 1 to 20. Examples of the hydrocarbon group include alkyl groups having 1 to 20 carbon atoms, such as methyl groups, ethyl groups, and propyl groups; alkenyl groups having 2 to 20 carbon atoms, such as vinyl groups and allyl groups; and alkylidene groups having 2 to 20 carbon atoms, such as ethylidene groups and propylidene groups. The hydrocarbon group may contain an oxygen atom or a halogen atom. 1 ~R 18 Each of the is independently preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, more preferably a hydrogen atom or a methyl group, and most preferably a hydrogen atom.
[0055] In formula (1), X is a single bond or a divalent organic group, and the organic group is, for example, -CO-O-CH 2 -It is.
[0056] Examples of the compound represented by formula (1) include a compound represented by the following formula (1a) and a compound represented by the following formula (1b).
[0057] [ka]
[0058] [ka]
[0059] [ka]
[0060] In formula (20), R 1 ~R 12are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group having 1 to 20 carbon atoms. The halogen atom is, for example, a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom. The hydrocarbon group having 1 to 20 carbon atoms is, for example, an alkyl group having 1 to 20 carbon atoms such as a methyl group, an ethyl group, or a propyl group; an alkenyl group having 2 to 20 carbon atoms such as a vinyl group or an allyl group; or an alkylidene group having 2 to 20 carbon atoms such as an ethylidene group or a propylidene group. The hydrocarbon group having 1 to 20 carbon atoms may contain an oxygen atom or a halogen atom.
[0061] R 1 ~R 12 Each of the is independently preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, more preferably a hydrogen atom or a methyl group, and most preferably a hydrogen atom.
[0062] An example of the compound represented by formula (20) includes the tetrahydroindene diepoxide represented by formula (20a) below.
[0063] [ka]
[0064] The polyfunctional heterocyclic epoxy compound contains, for example, a trifunctional epoxy compound as shown in the following formula (2).
[0065] [ka]
[0066] The polyfunctional oxetane compound contains, for example, a bifunctional oxetane compound as shown in the following formula (3).
[0067] [ka]
[0068] The alkylene glycol diglycidyl ether contains at least one compound selected from the group consisting of compounds represented by the following formulas (4) to (7).
[0069] [ka]
[0070] [ka]
[0071] [ka]
[0072] [ka]
[0073] The alkylene glycol monovinyl monoglycidyl ether contains, for example, a compound represented by the following formula (8).
[0074] [ka]
[0075] More specifically, the polyfunctional cationically polymerizable compound (W11) may contain at least one component selected from the group consisting of, for example, CELLOXIDE 2021P and CELLOXIDE 8010 manufactured by Daicel, TEPIC-VL manufactured by Nissan Chemical, OXT-221 manufactured by Toagosei, and 1,3-PD-DEP, 1,4-BG-DEP, 1,6-HD-DEP, NPG-DEP, and butylene glycol monovinyl monoglycidyl ether manufactured by Yokkaichi Chemical.
[0076] It is also preferred that the polyfunctional cationically polymerizable compound (W11) contains a polyfunctional alicyclic epoxy compound, in which case the composition (X) can have particularly high cationic polymerization reactivity.
[0077] The polyfunctional alicyclic epoxy compound preferably contains either one or both of the compound represented by formula (1) and the compound represented by formula (20). In this case, the composition (X) can have higher cationic polymerization reactivity.
[0078] When the polyfunctional alicyclic epoxy compound contains a compound represented by formula (1), the compound represented by formula (1) preferably contains a compound represented by formula (1a). In this case, the composition (X) can have a higher cationic polymerization reactivity and a particularly low viscosity.
[0079] In addition, since the compound represented by formula (20) has a low viscosity, the composition (X) can have good UV curing properties and a particularly low viscosity when the composition (X) contains the compound represented by formula (20). Furthermore, the compound represented by formula (20) has a low viscosity but is not easily volatilized. Therefore, even if the composition (X) contains the compound represented by formula (20), the composition (X) is not easily changed in composition due to the volatilization of the compound represented by formula (20). Therefore, the composition (X) can have a low viscosity without impairing storage stability by containing the compound represented by formula (20).
[0080] The compound represented by formula (20) can be synthesized, for example, by oxidizing a cyclic olefin compound having a tetrahydroindene skeleton with an oxidizing agent.
[0081] The compound represented by formula (20) may contain four stereoisomers based on the stereoconfiguration of the two epoxy rings. The compound represented by formula (20) may contain any of the four stereoisomers. That is, the compound represented by formula (20) may contain at least one component selected from the group consisting of the four stereoisomers. The percentage of the total amount of the exo-endo isomer and the endo-endo isomer among the four stereoisomers in the compound represented by formula (20) is preferably 10% by mass or less, more preferably 5% by mass or less, based on the total amount of the epoxy compound (A1). In this case, the heat resistance of the cured product can be improved. The percentage of a specific stereoisomer in the compound represented by formula (20) can be determined based on the peak area ratio appearing in a chromatogram obtained by gas chromatography.
[0082] In order to reduce the amount of exo-endo isomer and endo-endo isomer in the compound represented by formula (20), an appropriate method can be applied, such as a method of subjecting the compound represented by formula (20) to precision distillation or a method of applying column chromatography using silica gel or the like as a packing material.
[0083] When the composition (X) contains a polyfunctional cationic polymerizable compound (W11), the percentage of the polyfunctional cationic polymerizable compound (W11) relative to the total amount of the resin components is preferably 5% by mass or more and 95% by mass or less. The resin components refer to compounds having cationic polymerizability in the composition (X), and include the polyfunctional cationic polymerizable compound (W1) and the monofunctional cationic polymerizable compound (W2). If the percentage of the polyfunctional cationic polymerizable compound (W11) is 5% by mass or more, the composition (X) can have particularly excellent reactivity during the photocationic polymerization reaction, and the cured product can have high strength (hardness). If the percentage of the polyfunctional cationic polymerizable compound (W11) is 95% by mass or less, when the composition (X) contains a moisture absorbent (D), the moisture absorbent (D) can be particularly easily dispersed uniformly in the composition (X). The percentage of the polyfunctional cationic polymerizable compound (W11) is more preferably 12% by mass or more, even more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more. The percentage of the polyfunctional cationic polymerizable compound (W11) is more preferably 85% by mass or less, even more preferably 60% by mass or less. For example, the percentage of the polyfunctional cationic polymerizable compound (W11) is preferably within the range of 20 to 60% by mass.
[0084] When the polyfunctional cationic polymerizable compound (W11) contains a polyfunctional alicyclic epoxy compound, the polyfunctional alicyclic epoxy compound may be a part or the whole of the polyfunctional cationic polymerizable compound (W11). The percentage of the polyfunctional alicyclic epoxy compound to the polyfunctional cationic polymerizable compound (W11) is preferably 15% by mass or more and 100% by mass or less. When this percentage is 15% by mass or more, the polyfunctional alicyclic epoxy compound can particularly contribute to improving the ultraviolet curing property of the composition (X).
[0085] The polyfunctional cationic polymerizable compound (W12) has a siloxane skeleton and two or more cationic polymerizable functional groups per molecule. The number of cationic polymerizable functional groups per molecule of the polyfunctional cationic polymerizable compound (W12) is preferably 2 to 6, more preferably 2 to 4. The polyfunctional cationic polymerizable compound (W12) can contribute to improving the cationic polymerization reactivity of the composition (X) and can also contribute to improving the heat discoloration resistance of the cured product and optical components. The polyfunctional cationic polymerizable compound (W12) can also contribute to lowering the elastic modulus of the cured product and optical components. When the composition (X) contains a moisture absorbent, the polyfunctional cationic polymerizable compound (W12) can also contribute to improving the dispersibility of the moisture absorbent in the composition (X) and the cured product.
[0086] The polyfunctional cationically polymerizable compound (W12) is preferably a liquid at 25° C. In particular, the viscosity of the polyfunctional cationically polymerizable compound (W12) at 25° C. is preferably within the range of 10 to 300 mPa s. In this case, an increase in the viscosity of the composition (X) can be suppressed.
[0087] The cationically polymerizable functional group contained in the polyfunctional cationically polymerizable compound (W12) is, for example, at least one group selected from the group consisting of an epoxy group, an oxetane group, and a vinyl ether group.
[0088] The siloxane skeleton of the polyfunctional cationic polymerizable compound (W12) may be linear, branched, or cyclic. The number of Si atoms in the siloxane skeleton is preferably within the range of 2 to 14. In this case, the composition (X) can have a particularly low viscosity. The number of Si atoms is more preferably within the range of 2 to 10, even more preferably within the range of 2 to 7, and particularly preferably within the range of 3 to 6.
[0089] The polyfunctional cationically polymerizable compound (W12) contains, for example, at least one of a compound represented by formula (10) and a compound represented by formula (11).
[0090] [ka]
[0091] [ka]
[0092] In each of formulas (10) and (11), R is a single bond or a divalent organic group, and is preferably an alkylene group. Y is a siloxane skeleton, which may be linear, branched, or cyclic, and the number of Si atoms is preferably within a range of 2 to 14, more preferably within a range of 2 to 10, even more preferably within a range of 2 to 7, and particularly preferably within a range of 3 to 6. n is an integer of 2 or more, and is preferably within a range of 2 to 4.
[0093] More specifically, for example, the polyfunctional cationically polymerizable compound (W12) contains a compound represented by the following formula (10a).
[0094] [ka]
[0095] R in formula (10a) is a single bond or a divalent organic group, and is preferably an alkylene group having 1 to 4 carbon atoms. n in formula (10a) is an integer of 0 or more. n is preferably within the range of 0 to 12, more preferably within the range of 0 to 8, even more preferably within the range of 0 to 5, and particularly preferably within the range of 1 to 4.
[0096] The compound represented by formula (10a) preferably contains a compound represented by the following formula (30): That is, the polyfunctional cationically polymerizable compound (W12) preferably contains a compound represented by the following formula (30).
[0097] More specifically, the polyfunctional cationically polymerizable compound (W12) preferably contains at least one component selected from the group consisting of product numbers X-40-2669, X-40-2670, X-40-2715, X-40-2732, X-22-169AS, X-22-169B, X-22-2046, X-22-343, X-22-163, and X-22-163B manufactured by Shin-Etsu Chemical Co., Ltd.
[0098] The polyfunctional cationic polymerizable compound (W12) preferably has an alicyclic epoxy structure, and it is particularly preferred that the polyfunctional cationic polymerizable compound (W12) contains a compound represented by formula (10a). The compound represented by formula (10a) can particularly contribute to improving the cationic polymerization reactivity and lowering the viscosity of the composition (X), and can also particularly contribute to improving the heat discoloration resistance and lowering the elastic modulus of the cured product and optical components. When the composition (X) contains a moisture absorbent (D), it can also particularly contribute to improving the dispersibility of the moisture absorbent (D) in the composition (X).
[0099] When the composition (X) contains a polyfunctional cationic polymerizable compound (W12), the percentage of the polyfunctional cationic polymerizable compound (W12) relative to the total amount of the resin components is preferably 5% by mass or more and 95% by mass or less. In this case, when the composition (X) contains a moisture absorbent (D), the dispersibility of the moisture absorbent (D) in the composition (X) and in the cured product is particularly improved, and the composition (X) can have a particularly high photocationic polymerization reactivity.
[0100] The monofunctional cationically polymerizable compound (W2) has only one cationically polymerizable functional group per molecule. The cationically polymerizable functional group is, for example, at least one group selected from the group consisting of an epoxy group, an oxetane group, and a vinyl ether group.
[0101] The viscosity of the monofunctional cationic polymerizable compound (W2) at 25°C is preferably 8 mPa·s or less. In this case, even if the composition (X) does not contain a solvent, the monofunctional cationic polymerizable compound (W2) can reduce the viscosity of the composition (X). In particular, the viscosity of the monofunctional cationic polymerizable compound (W2) at 25°C is preferably within the range of 0.1 to 8 mPa·s.
[0102] The monofunctional cationically polymerizable compound (W2) may contain, for example, at least one compound selected from the group consisting of the compounds represented by the following formulas (12) to (17) and limonene oxide.
[0103] [ka]
[0104] [ka]
[0105] [ka]
[0106] [ka]
[0107] [ka]
[0108] [ka]
[0109] The percentage of the monofunctional cationic polymerizable compound (W2) relative to the total amount of the resin components is preferably 5% by mass or more and 50% by mass or less. If the percentage of the monofunctional cationic polymerizable compound (W2) is 5% by mass or more, the viscosity of the composition (X) can be particularly reduced. If the percentage of the monofunctional cationic polymerizable compound (W2) is 50% by mass or less, the composition (X) can have particularly excellent reactivity during the photocationic polymerization reaction, and the cured product can have high strength (hardness). The percentage of this monofunctional cationic polymerizable compound (W2) is more preferably 10% by mass or more, and even more preferably 15% by mass or more. The percentage of this monofunctional cationic polymerizable compound (W2) is more preferably 40% by mass or less, even more preferably 35% by mass or less, and particularly preferably 30% by mass or less. If the percentage of the monofunctional cationic polymerizable compound (W2) is particularly 35% by mass or less, the amount of volatilization of the components in the composition (X) during storage of the composition (X) can be effectively reduced, and therefore the properties of the composition (X) are less likely to be impaired even if the composition (X) is stored for a long period of time. Furthermore, the occurrence of tack in the cured product can be particularly suppressed. For example, it is preferable that the percentage of the monofunctional cationic polymerizable compound (W2) is within the range of 10 to 35% by mass.
[0110] In particular, when the composition (X) contains a polyfunctional cationic polymerizable compound (W11) and a polyfunctional cationic polymerizable compound (W12), the percentage of the polyfunctional cationic polymerizable compound (W11) is preferably 30% by mass or more and 60% by mass or less, the percentage of the polyfunctional cationic polymerizable compound (W12) is preferably 15% by mass or more and 30% by mass or less, and the percentage of the monofunctional cationic polymerizable compound (W2) is preferably 15% by mass or more and 40% by mass or less, based on the total amount of the resin components. In this case, the composition (X) can achieve a good balance of good storage stability, low viscosity, and good cationic polymerization reactivity, and further achieve a good balance of excellent transparency, excellent hygroscopicity, and high refractive index of the cured product.
[0111] When the cationically polymerizable compound (A2) contains a compound represented by formula (3) and a compound represented by formula (16), by adjusting the ratio of the two, it is possible to appropriately adjust the ease of progress of the curing reaction when preparing a photocured product from the composition (X), while achieving a low viscosity and improved storage stability of the composition (X).
[0112] The amount of the compound represented by formula (16) is appropriately adjusted so that the composition (X) has the above-mentioned properties. For example, the amount of the compound represented by formula (16) is preferably 10 mass% or more and 40 mass% or less based on the total amount of the resin components.
[0113] The cationically polymerizable compound (A2) preferably contains a compound (f1) represented by the following formula (30) (hereinafter also referred to as aromatic epoxy compound (f1)).
[0114] [ka]
[0115] In formula (30), X is at least one selected from the group consisting of halogen, H, a hydrocarbon group, and an alkylene glycol group, and when there are multiple Xs in one molecule, they may be the same or different. The hydrocarbon group is, for example, an alkyl group or an aryl group. When X is a hydrocarbon group, the number of carbon atoms in X is, for example, in the range of 1 to 10. R is a single bond or a divalent organic group. When R is a divalent organic group, the divalent organic group is, for example, an alkylene group, an oxyalkylene group, a carbonyloxyalkylene group (for example, -CO-O-CH 2 -), or -C(Ph) 2 -O-CH 2 - group. Y is H or a monovalent organic group. When Y is a monovalent organic group, the monovalent organic group can be, for example, an alkyl group or an aryl group.
[0116] When the cationic polymerizable compound (A2) contains an aromatic epoxy compound (f1), the aromatic epoxy compound (f1) has a low viscosity, so that the aromatic epoxy compound (f1) tends to lower the viscosity of the composition (X). In addition, the aromatic epoxy compound (f1) is not easily volatilized, so that even if the composition (X) is stored, the composition (X) is not easily changed in composition due to the volatilization of the aromatic epoxy compound (f1). Therefore, the aromatic epoxy compound (f1) tends to increase the storage stability of the composition (X). In addition, the aromatic epoxy compound (f1) has high reactivity, so that unreacted components are not easily left in the cured product, so that outgassing is not easily generated from the cured product. Furthermore, the aromatic epoxy compound (f1) tends to increase the glass transition temperature of the cured product, so that the heat resistance of the cured product is easily increased.
[0117] Furthermore, the aromatic epoxy compound (f1) is less likely to produce defective droplets called satellites when the composition (X) is discharged by an inkjet method.
[0118] R in formula (30) is preferably a single bond or an alkylene group. When n in formula (30) is 2 or 3, at least one of the multiple R in formula (30) is preferably a single bond or an alkylene group. In these cases, the reactivity of the aromatic epoxy compound (f1) tends to be high, and therefore the curability of the composition (X) tends to be high when the composition (X) is irradiated with ultraviolet light.
[0119] The aromatic epoxy compound (f1) preferably contains at least one compound selected from the group consisting of the compounds represented by the following formulas (301) to (318).
[0120] [ka]
[0121] In particular, it is preferred that the aromatic epoxy compound (f1) contains at least one component selected from the group consisting of the compounds represented by the formulas (301) to (305), (312), (314), and (318). These compounds tend to have high reactivity because at least one epoxy group (oxirane) in the compound is bonded to a benzene ring via a single bond or an alkylene group, and therefore tend to enhance the curability of the composition (X).
[0122] The percentage of the aromatic epoxy compound (f1) relative to the total amount of the cationic polymerizable compound (A2) is preferably 5% by mass or more. In this case, the above-mentioned effect of the aromatic epoxy compound (f1) is particularly easily obtained. This percentage is also preferably 95% by mass or less. In this case, the storage stability of the composition (X) is easily improved. This percentage is more preferably 10% by mass or more and 90% by mass or less, and even more preferably 20% by mass or more and 85% by mass or less.
[0123] The cationically polymerizable compound (A2) may contain a compound (f2) having an oxyalkylene skeleton. The oxyalkylene skeleton is a linear skeleton consisting of one or more linear oxyalkylene units.
[0124] When the cationic polymerizable compound (A2) contains the compound (f2), the compound (f2) has a low viscosity, and therefore the compound (f2) tends to lower the viscosity of the composition (X). In addition, the compound (f2) is not easily volatilized, and therefore, even if the composition (X) is stored, the composition (X) is not easily changed in composition due to the volatilization of the aromatic epoxy compound (f1). Therefore, the compound (f2) tends to increase the storage stability of the composition (X).
[0125] In addition, the compound (f2) is less likely to produce defective droplets called satellites when the composition (X) is discharged by the inkjet method. Furthermore, the compound (f2) can make it difficult for satellites to be produced even if the speed of the droplets discharged by the inkjet method is increased. Therefore, although it depends on the inkjet conditions, it is possible to make the discharge speed of the droplets by the inkjet method 4 m / s or more without producing satellites, for example. If the droplet speed can be increased, the trajectory of the droplets is less susceptible to disturbances, so that the dimensional accuracy of the cured product produced from the composition (X) can be improved. Furthermore, as described above, the compound (f2) can increase the storage stability of the composition (X), so that the characteristic of the composition (X) of being less likely to produce satellites is easily maintained even if the composition (X) is stored for a long period of time.
[0126] It is particularly preferable that the oxyalkylene skeleton contains a structure of "-CCO-", that is, an oxymethylene unit. In this case, satellites are particularly unlikely to be generated, and even if the driving frequency is changed when discharging the composition (X) by an inkjet method, satellites are unlikely to be generated. In addition, the compound (f2) is less likely to volatilize and is more likely to have a lower viscosity, and further, the affinity (wettability) of the composition (X) to inorganic materials is likely to be increased.
[0127] The number of oxyalkylene units in the oxyalkylene skeleton of compound (f2) is preferably 1 to 8. In this case, compound (f2) tends to have a lower viscosity, so that satellites are particularly unlikely to be generated, and the crosslink density of the cured product tends to be high, so that the glass transition temperature of the cured product tends to be particularly high. The number of oxyalkylene units is more preferably 1 to 6, and even more preferably 1 to 4.
[0128] In addition, the oxyalkylene unit in the oxyalkylene skeleton of the compound (f2) may have a substituent other than hydrogen bonded thereto. For example, the oxymethylene unit contained in the oxyalkylene skeleton may be "-CH(CH 3 )-CH 2 It may have the structure "-O-".
[0129] The percentage of the compound (f2) is preferably 10% by mass or more relative to the cationic polymerizable compound (A2). In this case, the inkjet property is good, and the wettability to the substrate is improved. It is also preferable that this percentage is 70% by mass or less. In this case, the glass transition temperature can be sufficiently increased. This percentage is more preferably 15% by mass or more and 60% by mass or less, and even more preferably 20% by mass or more and 50% by mass or less.
[0130] The compound (f2) contains, for example, at least one compound selected from a compound (f21) having an oxyalkylene skeleton and an epoxy group, and a compound (f22) having an oxyalkylene group and an oxetane group.
[0131] Compound (f21) contains at least one compound selected from the group consisting of, for example, the compound represented by the above formula (1b), the compound represented by formula (4), the compound represented by formula (5), the compound represented by formula (6), the compound represented by formula (7), the compound represented by formula (8), the compound represented by formula (13), the compound represented by formula (14), etc. Note that the components that compound (f21) can contain are not limited to the above.
[0132] Compound (f22) contains at least one compound selected from the group consisting of compounds represented by the above formula (3), compounds represented by formula (12), compounds represented by formula (16), and compounds represented by formula (17). Note that the components that compound (f22) can contain are not limited to the above.
[0133] The cationic polymerizable compound (A2) preferably contains a cyclic ether compound. The epoxy compound contains at least one compound selected from the compounds having a cyclic ether group that can be included in the cationic polymerizable compound (A2), for example.
[0134] The cyclic ether compound contains at least one of an epoxy compound and an oxetane compound. The epoxy compound contains at least one compound among the compounds having an epoxy group that can be contained in the above-mentioned cationic polymerizable compound (A2). The oxetane compound contains at least one compound among the compounds having an oxetane group that can be contained in the above-mentioned cationic polymerizable compound (A2).
[0135] When the cyclic ether compound contains an epoxy compound, the curing reaction is likely to proceed quickly when the composition (X) is irradiated with ultraviolet light, and the curability of the composition (X) is likely to be improved. The percentage of the epoxy compound to the total of the cationic polymerizable compound (A2) is preferably 20 mass% or more. In addition, the percentage of this epoxy compound is preferably 60 mass% or less.
[0136] In addition, when the cyclic ether compound contains an oxetane compound, the rapid progress of the reaction when the composition (X) is irradiated with ultraviolet light can be suppressed, making the cured product less likely to turn yellow or become cloudy, and the reaction can be allowed to proceed sufficiently to make the cured product less likely to generate outgas. The percentage of the oxetane compound relative to the total amount of the cationic polymerizable compound (A2) is preferably 40% by mass or more. In addition, this percentage is preferably 80% by mass or less.
[0137] When the composition (X) contains a cyclic ether compound, the cyclic ether compound may contain a water-soluble compound (C2) having a cyclic ether group which is at least a part of the water-soluble compound (C). The cyclic ether compound is inherently likely to impair the affinity between the composition (X) and the inorganic material, and therefore is likely to impair the flatness and smoothness of the coating film and the cured product formed on the inorganic material. However, when the cyclic ether compound contains the water-soluble compound (C2), the surfaces of the coating film and the cured product are likely to be flat and smooth even if the composition (X) contains a cyclic ether compound. The water-soluble compound (C2) contains, for example, at least one of a water-soluble epoxy compound (C21) and a water-soluble oxetane compound (C22).
[0138] The water-soluble epoxy compound (C21) includes at least one selected from the group consisting of, for example, EX-145, EX-171, EX-810, and EX-920 manufactured by Nagase ChemteX Corporation; SR-PG, SR-EGM, and SR-2EG manufactured by Sakamoto Pharmaceutical Co., Ltd.; A-EP, DY-BP, and Epogosey BD(D) manufactured by Yokkaichi Synthetic Co., Ltd.; and Epolight 40E, Epolight 100E, Epolight 200E, and Epolight 400E manufactured by Kyoeisha Chemical Co., Ltd.
[0139] The water-soluble oxetane compound (C22) includes, for example, at least one selected from the group consisting of OXT-101 manufactured by Toagosei Co., Ltd., EXO and HBOX manufactured by Ube Industries, Ltd., and AL-OX manufactured by Yokkaichi Synthetic Co., Ltd.
[0140] When the composition (X) contains the cationic polymerizable compound (A2), the composition (X) preferably further contains a sensitizer. In this case, the composition (X) can have particularly high cationic polymerization reactivity. The sensitizer contains, for example, either one or both of 9,10-dibutoxyanthracene and 9,10-diethoxyanthracene. The percentage of the sensitizer relative to the cationic polymerizable compound (A2) is preferably in the range of more than 0 mass% and 1 mass% or less. In this case, the sensitizer is unlikely to inhibit the transparency of the cured product, and therefore the cured product can have good transparency.
[0141] When the composition (X) contains a cationic polymerizable compound (A2), the photopolymerization initiator (B) preferably contains a cationic photopolymerization initiator (B2). The cationic photopolymerization initiator (B2) is not particularly limited as long as it is a catalyst that generates a protonic acid or a Lewis acid upon irradiation with light. The cationic photopolymerization initiator (B2) can contain at least one of an ionic photoacid generating cationic curing catalyst and a nonionic photoacid generating cationic curing catalyst.
[0142] The ionic photoacid generating cationic curing catalyst may contain at least one of onium salts and organometallic complexes. Examples of onium salts include aromatic diazonium salts, aromatic halonium salts, and aromatic sulfonium salts. Examples of organometallic complexes include iron-arene complexes, titanocene complexes, and arylsilanol-aluminum complexes. The ionic photoacid generating cationic curing catalyst may contain at least one of these components.
[0143] The nonionic photoacid generating cationic curing catalyst may contain at least one component selected from the group consisting of nitrobenzyl ester, sulfonic acid derivative, phosphoric acid ester, phenolsulfonic acid ester, diazonaphthoquinone, and N-hydroxyimide phosphonate. However, the components that the nonionic photoacid generating cationic curing catalyst may contain are not limited to the above.
[0144] More specific examples of compounds that can contain the photocationic polymerization initiator (B2) include Midori Chemical's DPI series (105, 106, 109, 201, etc.), BI-105, MPI series (103, 105, 106, 109, etc.), BBI series (101, 102, 103, 105, 106, 109, 110, 200, 210, 300, 301, etc.), TSP series (102, 103, 105, 106, 109, 200, 300, 1000, etc.), HDS-109, MDS series (103, 105, 109, 203, 205, 209, etc.), BDS-109, MNPS-109, DTS series (102, 103, 105 , 200, etc.), NDS series (103, 105, 155, 165, etc.), DAM series (101, 102, 103, 105, 201, etc.), SI series (105, 106, etc.), PI-106, NDI series (105, 106, 109, 1001, 1004, etc.), PAI series (01, 101, 106, 1001, 1002, 1003, 1004, etc.), MBZ-101, PYR-100, NB series (101, 201, etc.), NAI series (100, 1002, 1003, 1004, 101, 105, 106, 109, etc.), TAZ series (100, 101, 102, 103, 104, 107, 10 8, 109, 110, 113, 114, 118, 122, 123, 203, 204, etc.), NBC-101, ANC-101, TPS-Acetate, DTS-Acetate, Di-Boc Bisphinol A, tert-Butyl lithocholate, tert-Butyl deoxycholate, tert-Butyl cholate, BX, BC-2, MPI-103, BDS-105, TPS-103, NAT-103, BMS-105, and TMS-105; Cyracure UVI-6970, Cyracure UVI-6974, Cyracure UVI-6990, and Cyracure UVI-950 manufactured by Union Carbide Corporation, USA; Irgacure 250, Irgacure 261 and Irgacure 264 from BASF; Ciba-Geigy CG-24-61; ADEKA Optomer SP-150, ADEKA Optomer SP-151, ADEKA Optomer SP-170 and ADEKA Optomer SP-171 manufactured by ADEKA Corporation; DAICAT II manufactured by Daicel Corporation; UVAC1590 and UVAC1591 manufactured by Daicel-Cytec Co., Ltd.; CI-2064, CI-2639, CI-2624, CI-2481, CI-2734, CI-2855, CI-2823, CI-2758, and CIT-1682 manufactured by Nippon Soda Co., Ltd.; PI-2074, tetrakis(pentafluorophenyl)borate toluylcumyl iodonium salt, from Rhodia; 3M FFC509; CD-1010, CD-1011 and CD-1012 manufactured by Sartomer, USA; CPI-100P, CPI-101A, CPI-110P, CPI-110A and CPI-210S manufactured by San-Apro Ltd.; and UVI-6992 and UVI-6976 manufactured by The Dow Chemical Company are included. The photocationic polymerization initiator (B2) may contain at least one compound selected from the group consisting of these compounds.
[0145] The percentage of the photocationic polymerization initiator (B2) relative to the cationic polymerizable compound (A2) is preferably 1% by mass or more and 4% by mass or less. When this percentage is 1% by mass or more, the composition (X) can have particularly good cationic polymerization reactivity. When this percentage is 4% by mass or less, the composition (X) can have good storage stability, and since it does not contain an excessive amount of the photocationic polymerization initiator (B2), it is possible to reduce the production cost.
[0146] The composition (X) may further contain a moisture absorbent (D). When the composition (X) contains the moisture absorbent (D), the cured product of the composition (X) can have moisture absorption properties. Therefore, the encapsulant 5 containing the cured product can further prevent moisture from penetrating into the light emitting element 4 in the light emitting device 1. The average particle size of the moisture absorbent (D) is preferably 200 nm or less. In this case, the cured product can have high transparency.
[0147] The moisture absorbent (D) is preferably an inorganic particle having moisture absorbing properties, and preferably contains at least one component selected from the group consisting of, for example, zeolite particles, silica gel particles, calcium chloride particles, and titanium oxide nanotube particles. It is particularly preferable that the moisture absorbent (D) contains zeolite particles.
[0148] Zeolite particles having an average particle size of 200 nm or less can be produced, for example, by pulverizing general industrial zeolite. In producing the zeolite particles, the zeolite may be pulverized and then crystallized by hydrothermal synthesis or the like, in which case the zeolite particles can have particularly high hygroscopicity. Examples of the method for producing such zeolite particles are disclosed in JP 2016-69266 A, JP 2013-049602 A, and the like.
[0149] The zeolite particles preferably contain sodium ions. Therefore, the zeolite particles are preferably made of at least one selected from the group consisting of A-type zeolite, X-type zeolite, and Y-type zeolite. It is particularly preferable that the zeolite particles are made of 4A-type zeolite among A-type zeolites. In these cases, the zeolite particles have a crystal structure suitable for adsorbing moisture.
[0150] The pH of the zeolite particles is preferably 7 or more and 10 or less. When the pH of the zeolite particles is 7 or more, the crystals of the zeolite particles are less likely to be destroyed, and therefore the cured product of the composition (X) containing the zeolite particles can have particularly high hygroscopicity. When the pH of the zeolite particles is 10 or less, the zeolite particles are less likely to hinder the curing of the composition (X) when it is cured. The pH of the zeolite particles is a value obtained by heating a dispersion obtained by adding 0.05 g of zeolite particles to 99.95 g of ion-exchanged water at 90°C for 24 hours, and then measuring the pH of the supernatant of the dispersion with a pH meter. Examples of pH meter include a compact pH meter manufactured by Horiba, Ltd. <laquatwin>B-711 can be used.
[0151] The average particle size of the moisture absorbent (D) is preferably 10 nm or more and 200 nm or less. If the average particle size is 200 nm or less, the cured product can have particularly high transparency. If the average particle size is 10 nm or more, the moisture absorbent (D) can maintain good moisture absorption. Note that this average particle size is the median diameter calculated from the measurement results by dynamic light scattering method, that is, the cumulative 50% diameter (D50). Note that the Nanotrac Wave series from Microtrack Bell Co., Ltd. can be used as a measuring device.
[0152] The average particle size of the moisture absorbent (D) is preferably 150 nm or less, more preferably 100 nm or less, and particularly preferably 70 nm or less. The average particle size of the moisture absorbent (D) is preferably 20 nm or more, and more preferably 50 nm or more. In this case, the cured product can have particularly good transparency and moisture absorption.
[0153] It is also preferable that the cumulative 90% diameter (D90) of the moisture absorbent (D) is 100 nm or less. In this case, the cured product can have particularly high transparency.
[0154] When the composition (X) contains the moisture absorbent (D), the percentage of the moisture absorbent (D) relative to the total amount of the composition (X) is preferably 1% by mass or more and 20% by mass or less. If the percentage of the moisture absorbent (D) is 1% by mass or more, the cured product can have particularly high moisture absorption. If the percentage of the moisture absorbent (D) is 20% by mass or less, the viscosity of the composition (X) can be particularly reduced, and the composition (X) can have a sufficiently low viscosity that can be applied by the inkjet method. The percentage of the moisture absorbent (D) is more preferably 3% by mass or more, and particularly preferably 5% by mass or more. The percentage of the moisture absorbent (D) is more preferably 15% by mass or less, and particularly preferably 13% by mass or less.
[0155] The composition (X) may further contain an inorganic filler other than the moisture absorbent (D). For example, the composition (X) may contain nano-sized high refractive index particles. Examples of high refractive index particles include zirconia particles. When the composition (X) contains high refractive index particles, the refractive index of the cured product can be increased while maintaining good transparency of the cured product. Therefore, when the cured product is applied to an optical component, the extraction efficiency of light that passes through the optical component and is emitted to the outside can be improved. The average particle size of the high refractive index particles is preferably within the range of 5 to 30 nm, and more preferably within the range of 10 to 20 nm.
[0156] The percentage of the high refractive index particles in the composition (X) is appropriately designed so that the cured product has a desired refractive index. In particular, the high refractive index particles are preferably contained in the composition (X) so that the refractive index of the cured product is in the range of 1.45 or more and less than 1.55. In this case, the light extraction efficiency of the light emitting device 1 is particularly improved.
[0157] When the composition (X) contains the moisture absorbent (D), the composition (X) preferably further contains a dispersant (E). In this case, the dispersant (E) can improve the dispersibility of the moisture absorbent (D) in the composition (X). Therefore, the composition (X) is less likely to suffer from the increase in viscosity and the decrease in storage stability caused by the moisture absorbent (D).
[0158] The dispersant (E) is a surfactant that can be adsorbed to particles. The dispersant (E) has an adsorption group (generally called an anchor) that can be adsorbed to particles, and a molecular skeleton (generally called a tail) that adheres to the particles by the adsorption of the adsorption group to the particles. The dispersant (E) contains at least one component selected from the group consisting of, for example, an acrylic dispersant whose tail is an acrylic molecular chain, a urethane dispersant whose tail is a urethane molecular chain, and a polyester dispersant whose tail is a polyester molecular chain. The adsorption group includes at least one of, for example, a basic polar functional group and an acidic polar functional group. The basic polar functional group includes at least one group selected from the group consisting of, for example, an amino group, an imino group, an amide group, an imide group, and a nitrogen-containing heterocyclic group. The acidic polar functional group includes at least one group selected from the group consisting of, for example, a carboxyl group and a phosphate group. The dispersant (E) may contain at least one compound selected from the group consisting of, for example, the Solsperse series manufactured by Nippon Louvre Resol Co., Ltd., the DISPERBYK series manufactured by BYK-Chemie Japan Co., Ltd., and the AJISPER series manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0159] When the composition (X) contains a moisture absorbent (D), the amount of the dispersant (E) relative to 100 parts by mass of the moisture absorbent (D) is preferably 5 parts by mass or more and 60 parts by mass or less. When the amount of the dispersant (E) is 5 parts by mass or more, the function of the dispersant (E) can be effectively expressed, and when the amount is 60 parts by mass or less, the free molecules of the dispersant (E) in the cured product can be prevented from inhibiting the adhesion between the cured product and the inorganic material member. In addition, the amount of the dispersant (E) is more preferably 15 parts by mass or more, more preferably 50 parts by mass or less, even more preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less.
[0160] The structure of the light emitting device 1 will be described. The light emitting device 1 includes a light source and an optical component that transmits the light emitted by the light source. For example, the light emitting device 1 includes a light emitting element 4, and a sealant 5 and a passivation layer 6 that cover the light emitting element 4. In this case, the light emitting element 4 is the light source, the sealant 5 is the optical component, and the passivation layer 6 is an inorganic layer such as a silicon nitride film. The sealant 5 and the passivation layer 6 overlap each other.
[0161] The light-emitting element 4 includes, for example, a light-emitting diode. The light-emitting diode includes, for example, at least one of an organic EL element (organic light-emitting diode) and a micro light-emitting diode. When the light-emitting element 4 includes an organic light-emitting diode, the light-emitting device 1 including the light-emitting element 4 is, for example, an organic EL display. When the light-emitting element 4 includes a micro light-emitting diode, the light-emitting device 1 including the light-emitting element 4 is, for example, a micro LED display. Note that EL is an abbreviation for electroluminescence.
[0162] An example of the structure of the light emitting device 1 will be described with reference to Fig. 1. This light emitting device 1 is a top emission type. The light emitting device 1 includes a support substrate 2, a transparent substrate 3 that faces the support substrate 2 with a gap therebetween, a light emitting element 4 on the surface of the support substrate 2 that faces the transparent substrate 3, and a passivation layer 6 and a sealing material 5 that cover the light emitting element 4.
[0163] The support substrate 2 is made of, for example, but not limited to, a resin material. The transparent substrate 3 is made of a material having light-transmitting properties. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate. The light-emitting element 4 includes, for example, a pair of electrodes 41, 43 and an organic light-emitting layer 42 between the electrodes 41, 43. The organic light-emitting layer 42 includes, for example, a hole injection layer 421, a hole transport layer 422, an organic light-emitting layer 423, and an electron transport layer 424, which are stacked in the above order.
[0164] The light emitting device 1 includes a plurality of light emitting elements 4, which form an array 9 (hereinafter referred to as element array 9) on a support substrate 2. The element array 9 also includes a partition 7. The partition 7 is located on the support substrate 2 and separates two adjacent light emitting elements 4. The partition 7 is produced, for example, by forming a photosensitive resin material using a photolithography method. The element array 9 also includes connection wiring 8 that electrically connects the electrodes 43 and the electron transport layers 424 of adjacent light emitting elements 4 to each other. The connection wiring 8 is provided on the partition 7.
[0165] The passivation layer 6 is preferably a silicon nitride film or a silicon oxide film, and is particularly preferably a silicon nitride film. In the example shown in FIG. 1, the passivation layer 6 includes a first passivation layer 61 and a second passivation layer 62. The first passivation layer 61 covers the element array 9 in a state of direct contact with the element array 9, thereby covering the light-emitting element 4. The second passivation layer 62 is disposed on the opposite side of the element array 9 with respect to the first passivation layer 61, and a gap is provided between the second passivation layer 62 and the first passivation layer 61. The sealant 5 is filled between the first passivation layer 61 and the second passivation layer 62. That is, the first passivation layer 61 is interposed between the light-emitting element 4 and the sealant 5 covering the light-emitting element 4.
[0166] Furthermore, a second sealing material 52 is filled between the second passivation layer 62 and the transparent substrate 3. The second sealing material 52 is made of, for example, a transparent resin material. The material of the second sealing material 52 is not particularly limited. The material of the second sealing material 52 may be the same as or different from the sealing material 5.
[0167] A method for producing the encapsulant 5 using the composition (X) and a method for producing the light emitting device 1 will be described.
[0168] In this embodiment, it is preferable to form the composition (X) by the inkjet method, and then irradiate the composition (X) with ultraviolet light to harden the composition (X), thereby producing the encapsulant 5. In this embodiment, the composition (X) can be applied and formed by the inkjet method. As described above, in this embodiment, the percentage of oxygen in the composition (X) is 75 mass % or less, and therefore defects are unlikely to occur when the composition (X) is formed by the inkjet method.
[0169] More specifically, for example, first, the support substrate 2 is prepared. On one surface of the support substrate 2, the partition walls 7 are formed by, for example, photolithography using a photosensitive resin material. Then, a plurality of light-emitting elements 4 are provided on one surface of the support substrate 2. The light-emitting elements 4 can be formed by an appropriate method such as a deposition method or a coating method. In particular, it is preferable to form the light-emitting elements 4 by a coating method such as an inkjet method. In this way, an element array 9 is formed on the support substrate 2. The tops of the partition walls 7 protrude from the surfaces of the light-emitting elements 4, and the dimension from the surface of the light-emitting elements 4 to the tops of the partition walls 7 is, for example, 0.1 μm or more and 1.5 μm or less. The interval between adjacent partition walls 7 is, for example, 30 μm or more and 150 μm or less.
[0170] Next, a first passivation layer 61 is provided on the element array 9. The first passivation layer 61 can be formed by a deposition method such as a plasma CVD method.
[0171] The first passivation layer 61 is formed so as to cover the multiple light-emitting elements 4 and the partition walls 7. As described above, the tops of the partition walls 7 protrude beyond the surfaces of the light-emitting elements 4, and therefore the surface of the first passivation layer 61 has projections and recesses that follow the shapes of the partition walls 7.
[0172] Next, the composition (X) is applied, for example, by an inkjet method to form a coating film on the first passivation layer 61. If the inkjet method is applied to both the formation of the light-emitting element 4 and the application of the composition (X), the manufacturing efficiency of the light-emitting device 1 can be particularly improved.
[0173] As described above, in this embodiment, composition (X) contains 10 mass % or more of the water-soluble compound (C) and has a viscosity of 30 mPa s or less. Therefore, even if a coating film of composition (X) is formed on first passivation layer 61, which is a silicon nitride film or the like, and the surface of first passivation layer 61 has irregularities, the surface of the coating film is likely to be flat and smooth.
[0174] The coating film of the composition (X) is cured by irradiating it with ultraviolet light. In this way, the encapsulant 5, which is a cured film of the composition (X), is produced. The surface of the encapsulant 5 tends to be flat and smooth.
[0175] Next, a second passivation layer 62 is provided on the sealing material 5. The second passivation layer 62 can be formed by a deposition method such as a plasma CVD method.
[0176] Next, an ultraviolet-curable resin material is provided on one surface of the support substrate 2 so as to cover the second passivation layer 62, and then the transparent substrate 3 is placed on the resin material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate.
[0177] Next, ultraviolet light is irradiated from the outside toward the transparent substrate 3. The ultraviolet light passes through the transparent substrate 3 and reaches the ultraviolet-curable resin material. As a result, the ultraviolet-curable resin material is cured, and the second sealing material 52 is produced.
[0178] The thickness of the sealing material 5 is, for example, 50 μm or less. In this case, by thinning the sealing material 5, the light emitting device 1 can be thinned, and it is also possible to obtain a light emitting device 1 having flexibility. In addition, in this embodiment, the surface of the sealing material 5 is likely to be flat and smooth, so that even if the thickness of the sealing material 5 is 15 μm or less, a sealing material 5 having a flat and smooth surface is likely to be obtained. The thickness of the sealing material is more preferably 10 μm or less, and even more preferably 5 μm or less. In addition, in order to effectively suppress moisture to the light emitting element 4 by the sealing material 5, the thickness of the sealing material 5 is preferably 1 μm or more, and more preferably 2 μm or more.
[0179] The thickness of the passivation layer 6 overlapping the sealing material 5 is, for example, 0.1 μm or more and 2 μm or less. When the passivation layer 6 includes the first passivation layer 61 and the second passivation layer 62 as described above, it is preferable that the thickness of each of the first passivation layer 61 and the second passivation layer 62 is 0.1 μm or more and 2 μm or less.
[0180] The use of the composition (X) according to this embodiment is not limited to the preparation of the encapsulant 5 for the light-emitting element 4. The composition (X) can be used to prepare various optical components that transmit light emitted by a light source. For example, the optical component may be a color resist. That is, for example, a phosphor may be contained in the composition (X), and a color resist in a color filter may be prepared on an inorganic material from the composition (X). This color filter can be provided in a display device such as an organic EL display or a micro LED display, which is a light-emitting device. EXAMPLES
[0181] 1. Preparation of the Composition Compositions of the examples and comparative examples were prepared by mixing the components shown in the table below.
[0182] The details of the components shown in the table are as follows. The viscosity of each component was measured using a rheometer (Anton Paar Japan, model number DHR-2) at a temperature of 25°C and a shear rate of 1000 s -1 The values were measured under the following conditions. -Epoxy compound 1: Water-insoluble, compound name: tetrahydroindene diepoxide, manufactured by ENEOS Corporation, product name: THI-DE, viscosity: 20 mPa·s. -Epoxy compound 2: Water-soluble, 1,4-butanediol diglycidyl ether, manufactured by Yokkaichi Synthetic Co., Ltd., product name Epogose BD (D), viscosity 8.4 mPa s. -Epoxy compound 3: Water-soluble, ethylene glycol diglycidyl ether, manufactured by Kyoeisha Chemical Co., Ltd., product name Epolite 400E, viscosity 85 mPa·s. -Oxetane compound 1: water-insoluble 3-ethyl-3-{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane (compound shown in formula (3)), manufactured by Toagosei Co., Ltd., product number OXT-221, viscosity 10 mPa·s. -Oxetane compound 2: Water-soluble, 3-ethyl-3-hydroxymethyloxetane (oxetane alcohol), manufactured by Toagosei Co., Ltd., product number OXT-101, viscosity 19.5 mPa s. -Oxetane compound 3: Water-soluble, (3-ethyl-3-(4-hydroxybutyloxymethyl)oxetane, manufactured by Ube Industries, Ltd., product number ETERNACOLL (registered trademark) HBOX, viscosity 29 mPa·s. -Photopolymerization initiator: Triarylsulfonium salt-based photoacid generator, San-Apro Co., Ltd., product number CPI-210S. Sensitizer: Kawasaki Chemical Industries, Ltd., product name Anthracure (registered trademark) UVS1331. -Leveling agent: Phenyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd., product name KBM-103.
[0183] 2.Evaluation Test The following evaluation tests were carried out on the examples and comparative examples, and the results are shown in the table below.
[0184] (1) Flatness / Smoothness (Urokomura) A prebaked film was produced by applying a photosensitive polyimide resin (manufactured by Toray, product name Photoneece DL-1000) onto a glass substrate and then heating it at 120°C for 3 minutes using a hot plate. The thickness of the prebaked film was measured using a Hitachi High-Technologies spectrophotometer (U-4100) and found to be 2 μm. This prebaked film was exposed to light through a photomask, developed by exposing it to a developer (a 2.38% by mass solution of tetramethylammonium hydroxide) for 60 seconds, and then heated at 250°C for 60 minutes in a clean oven. As a result, a partition wall (black matrix) with a height of 0.5 μm arranged in a lattice pattern was produced on the glass substrate. The planar dimensions of the opening surrounded by the partition wall were 70 μm x 250 μm.
[0185] A silicon nitride film having a thickness of 500 nm was formed on the entire surface of the glass substrate on which the partition walls had been formed so as to cover the partition walls.
[0186] The composition was placed in the cartridge of an inkjet printer (FUJIFILM Corporation, Material Printer MP2831), and after confirming that the composition in the cartridge could be ejected from the nozzle of the inkjet printer, droplets of the composition were ejected from the nozzle at 600 dpi to produce a coating film with a maximum thickness of 5 μm.
[0187] Five minutes after the coating was made, the coating was irradiated in dry air with an LED-UV irradiator manufactured by CCS Inc. at a peak wavelength of 395 nm and an output of 100 mW / cm. 2 , cumulative light intensity 1500mJ / cm 2 The coating film was photocured by irradiating it with light under the above conditions to prepare an encapsulant.
[0188] The coating film was observed immediately before being irradiated with light 5 minutes after its preparation, and a coating film with a flat surface was rated as "A".
[0189] If the coating was not evaluated as "A", the coating was left for 20 minutes without being irradiated with light after preparation and then observed. If the surface of the coating was flat, it was evaluated as "B", and if the surface of the coating was wavy, it was evaluated as "C".
[0190] (2) Viscosity The viscosity of the composition was measured using a rheometer (Anton Paar Japan, model number DHR-2) at a temperature of 25°C and a shear rate of 1000 s -1 The measurements were performed under the following conditions.
[0191] (3) Transmittance The composition was applied to prepare a coating film having a thickness of 10 μm, and ultraviolet rays were irradiated to the coating film at 3 W / cm under atmospheric conditions using an LED-UV irradiator manufactured by Ushio Inc. (model number E075IIHD, peak wavelength 395 nm). 2 A film was produced by irradiating the film with an irradiation intensity of 100° C. for 5.3 seconds and then heating the film for 5 minutes at 100° C. The total light transmittance of the film was measured according to JIS K7361-1.
[0192] (4) Inkjet compatibility The composition was placed in the cartridge of an inkjet printer (Fujifilm, Model DMP2831), and droplets of the composition were ejected from the nozzle of the inkjet printer at a temperature of 30° C. and a frequency of 1 kHz. The droplets were observed with a high-speed camera, and were rated as "A" when neither mist nor satellites were observed, and "B" when at least one of mist or satellites was observed.
[0193] (5) Glass transition temperature The composition was applied to prepare a coating film, and the coating film was irradiated with ultraviolet light at an intensity of 5 W / cm using a Unijet E075IIHD (peak wavelength 395 nm) manufactured by Ushio Electric Co., Ltd. in an air atmosphere. 2 , and the cumulative light intensity is 5000mJ / cm 2 The coating was photocured by irradiating the coating under the conditions of , and a film having a thickness of 200 μm was produced. The glass transition temperature of a sample cut out from this film was measured using a viscoelasticity measuring device (manufactured by Hitachi High-Tech Science Corporation, model number DMA7100).
[0194] (6) Outgassing evaluation The outgassing when the cured product of the composition was heated was sampled by the headspace method and measured by gas chromatography. In detail, 100 mg of the composition was placed in a headspace vial with a volume of 22 mL. Next, the composition was irradiated with ultraviolet light at an intensity of 5 W / cm using a Unijet E075IIHD (peak wavelength 395 nm) manufactured by Ushio Inc. under an atmospheric condition. 2 , and the cumulative light intensity is 1500mJ / cm 2 The composition was cured by irradiating the composition under the conditions of 100°C, and the vial was then sealed. The composition was then heated at 100°C for 30 minutes, and the gas phase in the vial was then introduced into a gas chromatograph for analysis. As a result, the concentration of outgassing generated from the composition was determined based on the peak area of the resulting gas chromatogram. The concentration of outgassing is the volume fraction of outgassing in the gas phase of the vial relative to the volume of the vial (22 mL).
[0195] The outgas concentrations were determined using toluene as a reference substance. Specifically, two reference samples with toluene concentrations of 1000 ppm and 100 ppm were prepared by volatilizing toluene in a vial. Each reference sample was introduced into a gas chromatograph for analysis. From the peak areas of the two chromatograms obtained in this way, the relationship between the peak area and the concentration was determined, and the above outgas concentrations were determined based on these results.
[0196] As a result, the outgas concentration (volume fraction) was rated as "A" when it was 50 ppm or less, "B" when it was more than 50 ppm and 100 ppm or less, "C" when it was more than 100 ppm and 200 ppm or less, and "D" when it was more than 200 ppm.
[0197] [Table 1] < / laquatwin>
Claims
1. The ultraviolet-curable resin composition contains a photopolymerizable compound (A), a photopolymerization initiator (B), and a sensitizer, the photopolymerizable compound (A) contains a water-soluble compound (C), and the percentage of the water-soluble compound (C) relative to the ultraviolet-curable resin composition is 10 mass% or more; The viscosity at 25°C is 30 mPa·s or less, The photopolymerizable compound (A) contains a cationic polymerizable compound (A2), The cationically polymerizable compound (A2) contains a cyclic ether compound, The cyclic ether compound contains an epoxy compound and an oxetane compound, The epoxy compound contains a water-soluble epoxy compound (C21), the percentage of the water-soluble epoxy compound (C21) relative to the oxetane compound is 10 / 60 mass% or more and 50 mass% or less; The sensitizer contains either one or both of 9,10-dibutoxyanthracene and 9,10-diethoxyanthracene. UV curable resin composition.
2. The percentage of the water-soluble compound (C) relative to the photopolymerizable compound (A) is 50 mass% or less. The ultraviolet-curable resin composition according to claim 1 .
3. To produce an optical component that transmits light emitted by a light source, The ultraviolet-curable resin composition according to claim 1 or 2.
4. Formed by the inkjet method, The ultraviolet-curable resin composition according to claim 1 .
5. A cured product of the ultraviolet-curable resin composition according to any one of claims 1 to 4. Optical components.
6. The method includes molding the ultraviolet-curable resin composition according to any one of claims 1 to 4 by an inkjet method, and then irradiating the ultraviolet-curable resin composition with ultraviolet light to cure the composition. A method for manufacturing optical components.
7. Fabricating the optical component on a silicon nitride film; The method for producing the optical component according to claim 6 .
8. A light source and an optical component that transmits light emitted by the light source, the optical component including a cured product of the ultraviolet-curable resin composition according to any one of claims 1 to 4. Light emitting device.
9. Further comprising a silicon nitride membrane; the optical component overlies the silicon nitride membrane; The light emitting device according to claim 8.
10. A method for manufacturing a light emitting device including a light source and an optical component that transmits light emitted by the light source, comprising the steps of: The optical component is manufactured by the method according to claim 6 or 7. A method for manufacturing a light emitting device.
Citation Information
Patent Citations
Method of manufacturing electronic device
JP2008059945A
Organic el laminate
JP2014186850A
Sealing agent for organic el display element
JP2019029355A
Organic electronic devices
JP2020521300A
